2020
DOI: 10.1016/j.hrtlng.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width is associated with mortality risk in patients with acute respiratory distress syndrome based on the Berlin definition: A propensity score matched cohort study

Abstract: Background: Acute respiratory distress syndrome (ARDS) is a severe inflammatory disorder of the lungs and is associated with oxidative damage. However, red blood cell distribution width (RDW), as an indicator of body response to inflammation and oxidative stress, has not been studied for its relationship with ARDS as diagnosed by the Berlin definition. Objectives: To examine the value of RDW in predicting the prognosis of in patients with ARDS. Methods: This is a retrospective study based on the Medical Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…The authors also found that elevated RDW at index ED visit was associated with poor outcomes in CAP, including 30-date mortality, length of hospital stay, and need for vasopressors [ 16 ]. Moreover, our findings are in agreement with other data published in patients with other forms of ARDS not attributable to SARS-CoV-2 infection [ 17 ], as well as in an earlier publication on COVID-19 patients, characterized by a different setting and patient cohort. Regarding this latter study, Wang et al measured RDW in 45 COVID-19 patients with moderate and severe illness admitted to the Jingzhou Central Hospital from over a nearly 20-day period [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…The authors also found that elevated RDW at index ED visit was associated with poor outcomes in CAP, including 30-date mortality, length of hospital stay, and need for vasopressors [ 16 ]. Moreover, our findings are in agreement with other data published in patients with other forms of ARDS not attributable to SARS-CoV-2 infection [ 17 ], as well as in an earlier publication on COVID-19 patients, characterized by a different setting and patient cohort. Regarding this latter study, Wang et al measured RDW in 45 COVID-19 patients with moderate and severe illness admitted to the Jingzhou Central Hospital from over a nearly 20-day period [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to our data, RDW is characterized by the highest χ 2 and OR for in-hospital mortality among all the variables considered. The clinical value of RDW is often neglected; in the last few years, it has been recognized as a common prognostic predictor in many human diseases: acute kidney injury, cancer, acute pancreatitis, and respiratory failure [36][37][38][39][40]. The predictive significance of RDW in the context of COVID-19 might reflect the effect on erythropoiesis of respiratory failure and systemic inflammation [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…An increased RDW value, which mirrors a large burden of anisocytosis in circulating erythrocytes, is now universally considered a strong and independent marker of many different RBC abnormalities that can be encountered in a vast array of human disorders [ 16 ]. Notably, some previous studies have found that increased RDW is associated with mortality in patients with nonspecific ARDS (i.e., without COVID-19) [ 17 , 18 , 19 ]. It is thus not surprising that these earlier findings could be confirmed in this meta-analysis, which clearly shows that RDW values are significantly higher in COVID-19 patients with severe illness than in those with mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), the pandemic infectious disease sustained by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues to spread unrelentingly around the world, being responsible for thousands of deaths each day. Despite the fact that SARS-CoV-2 is a predominantly respiratory pathogen, COVID-19 progresses as a multiple-phase and multifactorial disorder where an initial lung involvement is then accompanied by a systemic immunoinflammatory reaction (i.e., immunothrombosis), which culminates in the Acta Haematol 2021;144:360-364 DOI: 10.1159/000510914 risk of developing thrombosis, with lung (i.e., acute respiratory distress syndrome; ARDS) and distant multipleorgan injury [1,2].…”
Section: Introductionmentioning
confidence: 99%